Comparative evaluation of three diagnostic tests for detection of foot-andmouth disease virus of Indian origin* - LONGJAM, NEETA; SARMAH, A K; DEB, RAJIB; SAXENA, V K; TAYO, TILLING (The Indian Journal of Animal Sciences, 2012)
In the present study, we have comparatively evaluated 3 diagnostic tests, viz. virus isolation, sandwich ELISA and multiplex PCR to detect foot-and-mouth disease virus serotype ‘O’ in clinical samples, isolated from Indian origin. Our results showed that multiplex PCR could detect FMD virus in the highest number of samples than rest of the two comparatively.